REVITALISASI TPA PEH KABUPATEN JEMBRANA SEBAGAI TEMPAT PENGOLAHAN SAMPAH TERPADU - Sandy, Angelina Puspita; Aryanta, I Wayan Redi; Suarna, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2014)
Waste management in Jembrana District, had been handled by the Environmental Sanitation Department, which in 2012 the amount of garbage in Jembrana District it’s about 684.80 m3. The amount of garbage was large and continues to grow up every day, thus feared that TPA Peh will overload. This problem encourages the needed for Integrated Waste Sites Planning in TPA Peh, where it will accept the loads of Jembrana garbage. The Integrated Waste Site Planning in TPA Peh requires some studies, such as study of the technical aspects, financial aspects and environmental aspects. Based on technical analysis it was known that the garbage of Jembrana district in TPA Peh amounted to 150.56 m3/day. Recovery factor value was 80.33% with 19.87% residue. If this large amount of garbage is not processed, then TPA Peh predicted will be overloud in November 2015. By Integrated Waste Site Planning which is only the residue that wasted on landfill, then it could be extended the lifespan of the landfill until 9 (nine) years and 3 (three) month. Required area in the application of Integrated Waste Site Planning in TPA Peh is 13.701 m2. The total cost of investment in the implementation of the Integrated Waste Site in TPA Peh is Rp. 12.331.282.000.00. Total operational cost is Rp. 5.811.760.000, while the revenue potential of recycling such as composting and stalls selling stuff in 2022 is Rp. 18.390.154.291.56. Net Present Value (NPV) obtained positive value of Rp. 13.933.193.788 with a value of IRR is 45,23% and B / C ratio is 1,159. Environmental analysis on TPA Peh Jembrana by analysis of well water quality around the landfill, is known that most of the physical and chemical parameters are still under the quality standard. Biological parameters are still above the water quality standards based on Permenkes No. 416.Menkes/Per/IX/1990. From the analysis of landfill leachate water quality parameters known for Total Suspended Solids (TSS), Ammonium-free, BOD, COD and biological parameters are still higher then the effluent quality standards compared to Bali Governor Regulation No. 8 of 2007 on Environmental Quality Standards and Criteria Standard Environmental Damage.
Keywords: Technical, Financial and Environmental Analysis, Landfill, Integrated Waste Treatment Site